2014
DOI: 10.1002/ijc.28874
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cancers of unknown primary site: Results from the prospective EPIC cohort

Abstract: Cancer of unknown primary site (CUP) may be called an “orphan” disease, as it is diagnosed when metastases are detected while the primary tumor typically remains undetected, and because little research has been done on its primary causes. So far, few epidemiological studies, if any, have addressed possible risk factors for CUP. We analyzed data from the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort (N = 476,940). During prospective follow‐up, a total of 651 cases of incident cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 15 publications
6
70
0
1
Order By: Relevance
“…A recent European study published in this Journal showed that heavy smoking causes a risk of 3.66 for CUP patients of diverse and unspecified histologies; alcohol drinking and wide waist circumference were borderline risk factors. 2 The pathophysiology of CUP has remained an enigma, exemplified by the question presented in a review on CUP: "unknown primary or unknown biology?" 3 The inability to find a primary tumor may not merely depend on its small size but may involve newly described cell biological processes related to stem cell characteristics, microenvironment, immunoediting and senescence-apoptosis which may halt tumor growth and induce phenotypic changes.…”
Section: Dear Sirmentioning
confidence: 99%
“…A recent European study published in this Journal showed that heavy smoking causes a risk of 3.66 for CUP patients of diverse and unspecified histologies; alcohol drinking and wide waist circumference were borderline risk factors. 2 The pathophysiology of CUP has remained an enigma, exemplified by the question presented in a review on CUP: "unknown primary or unknown biology?" 3 The inability to find a primary tumor may not merely depend on its small size but may involve newly described cell biological processes related to stem cell characteristics, microenvironment, immunoediting and senescence-apoptosis which may halt tumor growth and induce phenotypic changes.…”
Section: Dear Sirmentioning
confidence: 99%
“…However, the period from the first visit to local physicians to being informed of diagnosis (Phase 2 to Phase 3) was longer in our patients with CUP. Especially, in our CUP cases, anxiety persisted with loneliness even after diagnosis, which was thought to derive from 'uncertainty' and 'orphan disease' characterizing CUP (24,25).…”
Section: Experience Of Patients With Cup Until Initial Treatmentmentioning
confidence: 99%
“…Therefore, the patients with CUP sometimes felt tensions for the relationship (data not shown). Supportive and nursing care needs to be provided beyond the otherwise disadvantageous situation of patients with CUP from outpatient visit period to in-hospital period in order to reduce psychological burden from loneliness by 'orphan' state (24).…”
Section: Experience Of Patients With Cup Until Initial Treatmentmentioning
confidence: 99%
“…There was also evidence that body mass index was inversely related to CUP with liver metastases which the authors speculated might be due to alcohol abuse. In the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, a total of 651 incident CUP patients were detected [ 24 ]. Risk of being diagnosed with CUP was strongly related to smoking, with a relative risk of 3.66 for current, heavy smokers (26+ cigarettes/day) compared to never smokers.…”
Section: Risk Factorsmentioning
confidence: 99%
“…For alcohol consumption and level of education, weaker associations were observed but they were no longer statistically signifi cant after adjusting for smoking and indices of obesity. The risk of CUP was increased by approximately 30 % for subjects in the highest versus lowest quartiles of waist circumference [ 24 ].…”
Section: Risk Factorsmentioning
confidence: 99%